INFLUENCE HYBRID RESOURCES TOWARD SUSTAINABILITY AT MICRO-HYDRO MANAGEMENT IN AMBAPA VILLAGE - Muhammad Yusan Naim (Journal of Environmental Engineering and Sustainable Technology, 2020)
This research illustrates the relationship analysis and influence of Hybrid Resources on the sustainable construct of Micro-hydro management. Hybrid Resources is an appropriate long-term solution in addressing the limitations of Micro-hydro Resources in the long dry season and is a variable that affects the sustainability of power plant management. The relationship and influence of these two constructs can be analyzed statistically inferential by applying Confirmatory Factor Analysis (CFA) partial and full model. The results of the partial model test showed that the estimation model of the reflection relationship of each of the variable Hybrid Resources and sustainability of its manifest variables had met the Critical Ratio (CR) and Standard Loading Factor (SLF) values. Furthermore, full-model test results show that the model estimation of relationship and influence between Hybrid Resources on sustainability variables is positive and significant and has fulfilled the criteria Of Good Of Fit (GOF). The most dominant manifest variable of gaining an indirect influence reflection of Hybrid Resources is of energy consumption of 0.746 and the manifest variable that most predominant gets reflection of the indirect influence of sustainability construct is the application of strict sanctions when properly proven use of the illegal energy by 0.704. The direct influence between Hybrid Resources against the sustainability construct by 0.260.